Current approaches to the intraocular correction of postoperative aphakia after corneal refractive surgery (a review) - Yu. A. Gusev; E. I. Belikova; E. B. Tret’yak; L. V. Zhezheleva (Oftalʹmologiâ, 2015)
Cataract surgery after radial keratotomy (RK) represents many challenges as many patients who had RK are now developing visually significant cataracts. Currently, cataract surgery is not only the exchange of opaque lens but a refractive procedure as well. Despite a huge armamentarium of diagnostic methods, intraocular lens (IOL) power calculations in these patients can be inaccurate and are associated with residual refractive errors for many reasons (overestimation of the corneal power by keratometry and corneal topography, errors in the assessment of effective lens position, inadequate selection of power calculation formulas). Methods based on refractive history which consider refraction and K values before corneal refractive surgery and its refractive result before cataract development as well as methods based on corneal topography are the most accurate methods to neutralize keratometry errors. Methods of «true» refraction estimation using correction coefficients which were calculated based on regression analysis of IOL implantation results after corneal refractive surgery are of significant importance as well. Patients with prior RK who undergo cataract surgery often require intraocular correction of astigmatism. The techniques include positioning and modifications of tunnel incision, anterior dosed keratotomy, excimer laser surgery, and toric IOL implantation. Finally, phaco technique should be carefully selected in patients with prior RK. Intraoperative dehiscence of RK incisions is the key challenge. 1.8‑2.2‑mm corneal incision placed between keratotomy incisions prevents this complication. In numerous keratotomy incisions, scleral tunnel is recommended.